1991
DOI: 10.1177/088307389100600114
|View full text |Cite
|
Sign up to set email alerts
|

Academic Underachievement in Children with Epilepsy

Abstract: Academic achievement was studied in 78 children with epilepsy, ages 5 to 13 years, to determine how seizures, treatment of seizures, and sociocultural factors influence academic achievement. Cognitive abilities were assessed with either the McCarthy Scales of Children's Abilities or the Wechsler Intelligence Scale for Children--Revised. Achievement was measured with the Peabody Individual Achievement Tests. Achievement scores were corrected for cognitive ability (IQ), and underachievement was defined as achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 25 publications
(5 reference statements)
4
77
0
Order By: Relevance
“…This is contrary to previous research, which has revealed an increased prevalence of behavioral and cognitive problems in children with epilepsy compared with those without. 13,36 This may be because the majority of epilepsy diagnoses in our cohort were either generalized idiopathic epilepsy, which is suggested to be associated with more mild impairments of social and educational function compared with other forms of epilepsy, 37 or "epilepsy unspecified" (convulsions, fits, or seizures not otherwise specified), which may capture children with more transient symptoms. Given the large body of research demonstrating adverse outcomes for children with epilepsy, we would caution against concluding from the findings of this study that epilepsy is not associated with developmental vulnerability for children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is contrary to previous research, which has revealed an increased prevalence of behavioral and cognitive problems in children with epilepsy compared with those without. 13,36 This may be because the majority of epilepsy diagnoses in our cohort were either generalized idiopathic epilepsy, which is suggested to be associated with more mild impairments of social and educational function compared with other forms of epilepsy, 37 or "epilepsy unspecified" (convulsions, fits, or seizures not otherwise specified), which may capture children with more transient symptoms. Given the large body of research demonstrating adverse outcomes for children with epilepsy, we would caution against concluding from the findings of this study that epilepsy is not associated with developmental vulnerability for children.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on the association between chronic illness and academic outcomes has mostly been on the basis of either specific pediatric samples, [12][13][14] or used informant reports of health status. 4,[7][8][9] Although providing important findings, these 2 designs have limitations in terms of the generalizability of results, and potential reporting bias, respectively.…”
mentioning
confidence: 99%
“…Associations between family functioning and a range of psychosocial and health outcomes in young people with epilepsy has also been demonstrated. Poorer levels of family functioning have been shown to predict higher levels of behavioral problems [9,10], lower self-esteem [11], social competencies [10,12], academic achievement [13,14], and treatment adherence [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al (19) found no differences in performance on cognitive measures between children with new-onset seizures before and after six months of treatment with AEDs compared to children with recently diagnosed diabetes mellitus. Increased seizure frequency has been negatively related to performance in some studies (7,(23)(24)(25)(26), although other studies found that seizure variables were not strongly related to academic achievement (2,4,14,27).To more clearly define the etiology and natural history of academic difficulties, longitudinal studies beginning early in the course of the seizure disorder are needed. To date, only four studies have examined academic problems among children with new-onset seizures, and in two of the studies (4,14) data on children with both new-onset and chronic seizures were combined and not reported separately.…”
mentioning
confidence: 99%
“…To date, only four studies have examined academic problems among children with new-onset seizures, and in two of the studies (4,14) data on children with both new-onset and chronic seizures were combined and not reported separately. Berg et al (28) enrolled children 1 month to 16 years of age into a study of new-onset epilepsy and reported academic progress at a 5-year followup.…”
mentioning
confidence: 99%